Role of UV irradiation in aetiopathogenesis of malignant melanoma - Wolnicka-Głubisz, Agnieszka; Płonka, Przemysław M. (Contemporary Oncology/Współczesna Onkologia, 2007)
UV irradiation has multiple effects on skin including erythema, immunosuppression and the induction of keratinocyte-derived skin cancers and cutaneous malignant melanoma. Cutaneous malignant melanoma, which arises from damage to the melanocytes, the pigment cells of the skin, is the most lethal of the skin cancers, known for its intractability to current therapies. Cutaneous malignant melanoma is associated in epidemiological studies with sun exposure of susceptible populations, especially children. In this review, we summarize the experimental information available on the role of UV radiation in melanoma and give an overview of a new melanoma model. Neonatally irradiated with UV, HGF/SF (hepatocyte growth factor/scatter factor) transgenic mice with age develop melanoma which recapitulates the aetiology, the histopathology and molecular pathogenesis of human disease. We also describe the role of melanin in the process of skin carcinogenesis. Melanin is the basic skin pigment present also in most types of melanoma. Studies on animal models for melanoma, especially HGF/SF transgenic mice, may help not only in understanding this lethal disease but also help to prevent it.